AMERICAN DREAM METAPHORICAL EXPRESSIONS IN THE GREAT GATSBY - Dwi Aji Prajoko (Universitas Muhammadiyah Surakarta, 2022)
Happiness is the goal of the American dream; a means to reach happiness is wealth; in the following turn, wealth cannot be gained without optimism, opportunities, and hard work. Meanwhile, the massive use of conceptual metaphor raises the question of whether all of the domains, namely optimism, opportunities, hard work, wealth, and happiness were expressed in metaphor in the Great Gatsby whose theme is the American dream. The data collection technique was document analysis. The data were differentiated from the non-data, taxonomized, analyzed their components, and analyzed their dominance. The results show that all domains of the American dream are expressed in all types of metaphors. Structural and ontological metaphors have slight differences in terms of sum. The orientational metaphor, however, has an extreme gap compared to the first two metaphors.Key words: American dream, metaphor, conceptual, expression